Effect of different handrail types and seat heights on kinematics and plantar pressure during STS in healthy young adults. Issue 49 (10th December 2021) - Han, Xiaolong; Xue, Qiang; Yang, Shuo; Zhang, Shouwei; Li, Min
Abstract : Abstract: Handrail type and seat height both significantly influence sit-to-stand (STS) movement. However, research on the associations between handrail type, seat height, and their cumulative effect on STS kinematics and changes in plantar pressure distribution during STS under different handrail types and seat heights is insufficient. The main objective of this study was to investigate the effect of different handrail types and seat heights on the kinematics and plantar pressure in healthy adults during STS. The study was conducted on 26 healthy young adults. Six conditions were tested: low seat (LS) and vertical handrail; LS and horizontal handrail (HH); LS and bilateral handrail; high seat (HS) and vertical handrail; HSHH; HS and bilateral handrail. The movement time, trunk tilt angle, and time from hindfoot to forefoot peak pressure were analyzed and compared. A significant difference was found in handrail type ( P < .001) and seat height ( P < .02) for the total movement time of STS. A significant difference was also found for the maximum trunk tilt angles ( P < .001) in handrail types. There was an interaction between handrail type and seat height for the time from hindfoot to forefoot peak pressure of STS ( P = .003). Using HSHH could take less time to accomplish STS movement; it also reduced the maximum trunk tilt angle and thus reduce the risk of falling; the time from hindfoot to forefoot peak pressure when using HSHH was short and subjects could accomplish STS movement easier.